ANALYSIS OF DIFFERENTIATION STRATEGY, PRICE. AND QUALITY PRODUCTS ON PURCHASE DECISION AT PAPA ONG COFFEEHOUSE - Iis Rahmadani; Otto Randa Payangan; Fauziah Umar (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
This study aims to analyze the effect of differentiation strategy, price, and product quality on purchasing decisions at Papa Ong coffee shop. The research method used is associative with multiple linear regression data analysis techniques. The research sample was taken randomly from consumers who visited the Papa Ong coffee shop. There were 50 respondents. The results of the data analysis showed that the differentiation strategy had a positive and significant influence on consumer purchasing decisions at the Papa Ong coffee shop. In addition, price also has a significant influence on purchasing decisions, where prices that are competitive and in accordance with the value provided by coffee shop products are important factors in influencing consumer purchasing decisions. Furthermore, product quality is also proven to have a significant influence on purchasing decisions, with consumers tending to choose products that have satisfactory quality. This research makes an important contribution to the understanding of the factors that influence consumer purchasing decisions at coffee shops. The practical implication of this research is that the Papa Ong coffee shop needs to pay attention to a unique differentiation strategy, set appropriate prices, and maintain product quality in order to influence consumer purchasing decisions more effectively.